Reliability of isometric mid-thigh pull for maximal strength testing in youth athletes: a systematic review - Bruno, J.; Montoro-Bombú, R.; Thapa, R. K.; Sarmento, H. (International Journal of Sports Science & Coaching, 2025)
The isometric mid-thigh pull (IMTP) is widely used for assessing maximal force production due to its minimal fatigue impact compared to dynamic strength tests. However, variations in testing protocols, equipment, and athlete characteristics may influence the reproducibility of IMTP-derived variables. Understanding its reliability in youth athletes is crucial for monitoring physical development and optimizing training programs. This systematic review followed PRISMA guidelines. A literature search in four databases (PubMed, SPORTDiscus, Scopus, Web of Science) identified studies on the test-retest reliability of IMTP in youth athletes (=21 years). Extracted data included participant characteristics, testing protocols, and reliability metrics (intraclass correlation coefficients [ICCs], coefficient of variation [CVs], and standard error of measurement [SEM]). Twenty studies met inclusion criteria (2095 athletes). Peak force reliability was high (ICCs = 0.72-0.99, CVs = 2.0%-8.3%). Early phase force outputs (e.g., force at 50 and 100 ms) showed greater variability (ICCs = 0.73-0.95, CVs = 5.5%-23.3%). IMTP exhibits good-to-excellent reliability for peak force in youth athletes but higher variability in early force measures. Standardizing testing protocols may enhance reliability. Despite methodological differences, IMTP remains a valuable tool for strength monitoring and talent identification in youth athletes.